Implementasi Nilai-Nilai Persatuan dan Kesatuan Wilayah untuk Antisipasi Pengaruh Arus Era Globalisasi - Muhammad Dzaky Fadli; Edy Soesanto (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This study aims to explore the values of Pancasila, specifically the 3rd principle (Unity of Indonesia), in maintaining and anticipating unity and integrity within the national territory in the era of globalization. Unity and integrity are closely related to human resources with a Pancasila-oriented character, emphasizing peaceful approaches, mutual respect, understanding, and appreciation of cultural diversity to foster a sense of family and kinship. The findings of this study reveal that Pancasila, particularly the 3rd principle, has provided a strong bond of unity and integrity amidst societal changes in the globalization era. Pancasila serves as a source of strength, guiding Indonesia toward a golden era as a dignified nation within the global civilization. It functions as a pillar of life across various sectors such as social, economic, political, cultural, and defense, steering the nation toward a Pancasila-characterized Republic of Indonesia (NKRI) to achieve a prosperous and advanced Indonesia.